An Ontology-Based Chatbot to Enhance Experiential Learning in a Cultural Heritage Scenario - Casillo, Mario; De Santo, Massimo; Mosca, Rosalba; Santaniello, Domenico (Frontiers in Artificial Intelligence, 2022)
Italy is rich in cultural attractions, many known worldwide, others more hidden and unrecognized. Cultural attractions include tangible cultural assets (works of art, archaeological excavations, churches) and intangible ones (music, poetry, art). Today, given the pervasive diffusion of "smart" devices, the intelligent use of modern technologies could play a crucial role in changing the habit of consulting and visiting cultural heritage mainly with traditional methodologies, making little or no use of the advantages coming from the more and more availability of digitalized resources. A realm of particular interest is "experiential learning" when applied to cultural heritage, where tourists more and more ask to be helped in discovering the richness of sites they explore. In this paper, we will present an innovative chatbot-based system, called HeriBot, that supports experiential tourism. Our system has been developed and experimented with a research effort for applying ICT technologies to enhance the knowledge, valorization, and sustainable fruition of the Cultural Heritage related to the Archaeological Urban Park of Naples (PAUN – Parco Archeologico Urbano di Napoli). Our paper starts exploiting the ontological approach based on a purpose ontology describing the Park Heritage. Using such an ontology, we designed a chatbot that can identify the specific characteristics and motivations of the tourist, defining language, tone, and visitable scenarios and, through the ontology, allows the visit to be transformed into a personalized educational opportunity. The system has been validated in terms of dialogue effectiveness and training efficiency by a panel of experts, and we present and discuss obtained results.